Effectiveness of Irrigation Protocols in Endodontic Therapy: An Umbrella Review - Manuel J. Orozco-Gallego; Eliana L. Pineda-Vélez; Wilder J. Rojas-Gutiérrez; Martha L. Rincón-Rodríguez; Andrés A. Agudelo-Suárez (Dentistry Journal, 2025)
Background: With the inclusion of evidence-based dentistry, numerous systematic reviews (SRs) and meta-analyses (MAs) have been conducted in endodontics with the best available scientific evidence to improve diagnosis and treatment. Objective: To synthesize the scientific evidence on the effectiveness of irrigation protocols in endodontic therapy. Methods: Following the umbrella review methodology (UR), a comprehensive literature search was conducted using scientific and grey literature databases. A quality evaluation and a descriptive analysis of the included SRs and MAs were conducted. Quantitative comparability between MAs was carried out. Results: Four descriptive SRs and nine MAs were included. Eight articles evidenced high methodological quality. Studies showed the effectiveness and efficacy depending on the study design, the findings of primary clinical trials, and factors related to the type of irrigant, concentration, volume, and irrigation systems. Variability between irrigants and protocols was observed. Follow-up periods extend from hours to years, and there were different study samples. SRs and MAs evidenced limitations regarding methodological aspects. Low overlap of the primary studies was found. Quantitative analyses indicated greater efficacy in microbial reduction and apical healing in favor of passive ultrasonic irrigation (PUI; RD −0.15; 95% CI −0.28, −0.01; p = 0.03; I2 = 60%; RD −0.09; 95% CI −0.16, −0.02; p = 0.01; I2 = 0%, respectively). Conclusions: This UR highlights the importance of root canal disinfection, emphasizing sodium hypochlorite (NaOCl) as the primary irrigant. Enhanced activation methods, such as PUI and lasers, improve irrigant efficiency, while alternatives like chlorhexidine (CHX) offer better biocompatibility. Standardized protocols and evidence-based clinical guidelines are needed. PROSPERO register: CRD42023409044.